1991
DOI: 10.1182/blood.v78.6.1538.1538
|View full text |Cite
|
Sign up to set email alerts
|

Administration of interleukin-2 (IL-2) results in increased plasma concentrations of IL-5 and eosinophilia in patients with cancer

Abstract: Peripheral eosinophilia is almost invariably observed during the course of interleukin-2 (IL-2) therapy and is frequently accompanied by the development of a capillary leak syndrome characterized by edema, weight gain, and oliguria. We studied five patients with advanced malignancy treated with IL-2. Eosinophilia was not present initially but developed in all patients late in the course of therapy, with counts ranging from 2,328/mm3 to 15,958/mm3. In all patients, there was a temporal relationship between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…During the Th1 state, early haemopoietic progenitors may still differentiate into the eosinophilic lineage in response to locally secreted IL-5. Also during therapeutic IL-2 administration, eosinophilia does not occur at the beginning of the treatment (van Haelst-Pisani et al, 1991). Final eosinophilic maturation and increased egress of eosinophils from the bone marrow may require additional T-cell-derived cytokine stimulation which occurs mainly during a Th2-type response.…”
Section: Discussionmentioning
confidence: 99%
“…During the Th1 state, early haemopoietic progenitors may still differentiate into the eosinophilic lineage in response to locally secreted IL-5. Also during therapeutic IL-2 administration, eosinophilia does not occur at the beginning of the treatment (van Haelst-Pisani et al, 1991). Final eosinophilic maturation and increased egress of eosinophils from the bone marrow may require additional T-cell-derived cytokine stimulation which occurs mainly during a Th2-type response.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the higher sensitivity of eosinophils to IL-5-induced priming of migratory responses might in most instances make the effect of IL-5 selective for eosinophils. In previous studies the concentration of IL-5 has been measured in plasma from asthmatic patients (7), patients with episodic angioedema and eosinophilia (22), and cancer patients treated with interleukin 2 (31), and in all cases the concentrations of IL-5 were in the picomolar range. Studies on receptors for IL-5 have revealed the presence of high-affinity receptors on eosinophils but not on neutrophils (6,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous IL-4, in contrast, up-regulated IL-5 and IL-13. As IL-5 and ¹ possibly ¹ IL-13 might be associated with some of the serious adverse effects of IL-2 immunotherapy [21], it appears that addition of IL-12 might relieve, and addition of IL-4 might enhance, these.…”
Section: Role Of Il-10 On Ifn-␥ Il-5 and Il-13 Production In Mncmentioning
confidence: 99%
“…These animals were characterized by a decreased number of eosinophils, which was responsible for a reduced immunity against helminths [19,20]. IL-5 is also produced in vivo during IL-2 immunotherapy in patients with cancer [3,21], and thus might be responsible for some of the side-effects of IL-2 therapy, namely hypotension and prerenal failure, capillary leakage, and pulmonary and peripheral oedema.…”
Section: Introductionmentioning
confidence: 99%